Combined Use of Aspirin and Statin is Associated With a Decreased Incidence of Hepatocellular Carcinoma. Issue 4 (21st April 2022) - Singh, Jasleen; Wozniak, Amy; Cotler, Scott J.; Dhanarajan, Asha; Aldrich, Daniel; Park, David; Kasia, Chris; Schmidt, Benjamin; Scaglione, Steven
Abstract : Background: Hepatocellular carcinoma (HCC) is a leading cause of cancer and cancer-related mortality worldwide. Studies have suggested that aspirin (ASA) and statins may be associated with a decrease in incident HCC. Goals: We aimed to evaluate the effect of ASA and statin use on the incidence of HCC in a prospective cohort of patients with liver cirrhosis and to identify if there was an increased risk of esophageal variceal hemorrhage (VH) in patients with ASA use. Study: We conducted a retrospective study of 521 patients with data collected from July 1, 2012 to December 31, 2017. We used competing risk analysis to assess the association between risk factors and HCC; and the association between ASA and VH. Results: ASA use alone was associated with a decreased incidence of HCC in the univariate and multivariate models; [hazard ratio (HR) confidence interval (CI): 0.348 (0.124-0.976); P =0.0448] and [HR (CI): 0.266 (0.094-0.755); P =0.0129, respectively]. The combination of ASA and statin use was associated with a decreased hazard of HCC [HR (CI): 0.15 (0.036-0.624); P =0.0090] and this remained statistically significant in the multivariable model [HR (CI): 0.113 (0.026-0.483); P =0.0033]. Among daily ASA users compared with non-users, there was not a significant increase in risk of VH. Conclusions: Daily ASA use was associated with a decrease risk of incident HCC. The combination of daily ASA use and statin use decreased the risk of incident HCC suggesting there is beneficial interaction. Finally, no excess VH was observed in daily ASA users compared with non-users.